ANALISIS PENERAPAN AKUNTANSI MANAJEMEN DALAM MENINGKATKAN KINERJA PERUSAHAAN - Denni Putra Manurung; Lincah Lestari Zai; Nelvi Sipayung; Hamonangan Siallagan (STKIP Subang, 2026)
This study aims to analyze the application of management accounting in improving company performance. Management accounting plays an important role in providing relevant information for management in the planning, control, and decision-making processes. The research method used is a descriptive qualitative method with a literature study and/or case study approach at certain companies. The data used comes from secondary sources such as financial reports, scientific journals, and other supporting documents. The results show that effective implementation of management accounting, such as the use of budgets, cost analysis, and management control systems, can improve operational efficiency and help companies achieve their strategic goals. In addition, information generated by management accounting can also help managers in identifying opportunities and risks faced by the company. The conclusion of this study is that management accounting plays a significant role in improving company performance, both financially and non-financially. Therefore, companies are advised to optimize the implementation of management accounting systems to support better decision-making and increase competitiveness in the market.